KONSEP DASAR PENGELOLAAN SATUAN PENDIDIKAN - Vera Ayu Nesti; Eka Setia Takwa; Fitriani, Fitriani; H. Muhammad Arafah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Management of an educational unit is an activity related to planning, organizing, implementing and supervising an educational unit so that management can run effectively and efficiently and to achieve the goals of education. This research aims to determine the basic concepts of educational unit management. The method used in this research is a literature study with data sources coming from reference books, journals, archives, documents, as well as previous research that is relevant to the topic being discussed. The results of this research are that the basic concept of education management must pay attention to various things, starting from the objectives and functions of management, objects in management, elements of management, as well as the scope of management of the educational unit itself. Education unit management has a broad scope, where management occurs from inside to outside the school. So it can be concluded that the management of educational units must pay attention to all these aspects so that management can run effectively, efficiently, and achieve the goals of education.